Study on Auxiliary Diagnosis of Depression Based on Gas Discharge Visualization Technology - Fei Gao; Liangsong Li; Qian Hu (Integrative Medicine Reports)
Objective: This study aims to identify unique characteristics of depression based on Gas Discharge Visualization (GDV) technology. Methods: A total of 120 participants with depressive symptoms (Group A) and 56 healthy controls (Group B) were assessed using GDV technology to identify energy value differences. Statistical analysis identified specific markers useful in confirming a diagnosis of depression. Results: Group A showed significantly lower energy values than Group B in all systems except the respiratory and urogenital systems (p < 0.05). Conversely, higher energy values were observed in the respiratory system’s throat, larynx, and trachea in Group A (p < 0.05). Within Group A, the lowest energy values were in the head, cardiovascular, and immune systems (p < 0.01), while the highest were in the respiratory and urogenital systems (p < 0.01). In the head, energy values were lower in the eyes (p < 0.05). Within the endocrine system, the thyroid showed the highest energy, and the epiphysis the lowest (p < 0.05). The transverse colon and duodenum exhibited the lowest energy in the digestive system (p < 0.001). The spine-lumbar zone and kidneys showed lower energy in their respective systems (p < 0.001). The throat, larynx, and trachea displayed the highest energy in the respiratory system (p < 0.001). Conclusion: GDV technology can be utilized for the auxiliary diagnosis of depression: Energy values are the lowest in the head, cardiovascular, and immune systems, and highest in the respiratory and urogenital systems. Lower energy values in the eyes within the head, with the thyroid and epiphysis marking the highest and lowest energy values in the endocrine system. The sacrum and the kidneys exhibited lower energy values within their respective systems, the transverse colon and duodenum had the lowest energy values within the digestive system. The throat, larynx, and trachea showed the highest energy values within the respiratory system.